EXPERIMENTAL RESEARCH OF SECOND ORDER REED-MULLER CODES - N.S. MOGILEVSKAYA; V.R. SKOROBOGAT; V.S. CHUDAKOV (Вестник Донского государственного технического университета, 2018)
In this paper given results of comparative experiments on research of correcting ability of two Reed-Muller codes likelihood decoders (Sidel'nikov-Pershakov decoder and Loidreau-Sakkour decoder) are presented. For reception of experimental results the program imitating model of the digital data link is realized.